1987
DOI: 10.1002/j.1460-2075.1987.tb04847.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression of the human growth hormone gene is conferred in part by the binding of a specific trans-acting factor.

Abstract: The molecular basis for the pituitary‐specific expression of the human growth hormone (hGH) gene was investigated, by gene transfer and protein footprinting experiments. Plasmid constructs in which CAT or Neo transcription units are fused to a 0.5 kb fragment of the hGH 5′ sequences were efficiently expressed in GC and GH3 cells, derived from a pituitary tumor, but not in cell lines of other origins, indicating the presence of a tissue‐specific promoter. DNaseI footprinting experiments have identified at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(100 citation statements)
references
References 47 publications
(44 reference statements)
6
93
0
1
Order By: Relevance
“…Members of the POU family are characterized by a DNA binding domain referred to as the POU domain [39]. Pit-1 is required for the terminal differentiation of somatotroph cells [40] and is responsible for the somatotroph-specific expression of GH [25]. It is interesting to note that Dlk1, a gene proposed to keep cells in an undifferentiated state [41] can repress the activity of a transcription factor known to promote terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Members of the POU family are characterized by a DNA binding domain referred to as the POU domain [39]. Pit-1 is required for the terminal differentiation of somatotroph cells [40] and is responsible for the somatotroph-specific expression of GH [25]. It is interesting to note that Dlk1, a gene proposed to keep cells in an undifferentiated state [41] can repress the activity of a transcription factor known to promote terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that the -90 to -70 region of the GH promoter contains a binding site for the transcription factor Pit-1/GHF-1 [25]. The overlap of the Pit-1 response element with the Dlk1 responsive region strongly implies that Dlk1-mediated GH repression occurs through a Pit-1-dependent mechanism.…”
Section: A Pit-1 Response Element Is Required For Dlk1-mediated Regulmentioning
confidence: 98%
See 1 more Smart Citation
“…It is mainly expressed in the pituitary and its expression is necessary for the normal differentiation, development and survival of three adenohypophysis cell types, thyrotrophs, somatotrophs and lactotrophs (Li et al, 1990;Simmons et al, 1990). It is also important for the proper expression of growth hormone (GH ), prolactin (PRL) (Lefevre et al, 1987;Nelson et al, 1988), thyroid-stimulating hormone (TSH ) (Li et al, 1990) and POU1F1 gene itself (Chen et al, 1990;McCormick et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Most exert their regulatory effects by binding specific nuclear regulatory proteins. Some of these proteins, such as GC2 [2,31 or its human homolog GHF2 [4], both later found to correspond to the well-known transcription factor Spl [5,61, clearly act as positive regulators of rGH gene transcription and are produced by numerous cell types. Others, such as Pit-1 [7, 81 (also called GC1 or GHFl) or the thyrotroph embryonic factor (TEF) [9], probably corresponding to a factor termed GC3 [2], also exert positive effects on GH gene transcription but are produced in a cell-specific manner only by pituitary cells.…”
mentioning
confidence: 99%